Penerapan Manajemen Risiko Kredit Pada Pembiayaan Syariah di Koperasi As Sakinah Sidoarjo - Laila, Nur (Universitas Muhammadiyah Surabaya, 2018)
Credit risk is one of the most frequent risks in tough financing such as on financing using ijarah and murabahah contracts in Sharia financial institutions. The reason is due to mistakes in the analysis of financing applications and lack of cooperative readiness in managing and anticipating the possibility of risk exposure in the institution. In other hand, sharia cooperatives follow the principle of lost and profit sharing that requires a careful cooperative in managing their business in order to achieve the expected profit target.As Sakinah Cooperation Sidoarjo which has been operating for 19 years only experienced credit risk less than 1%. Therefore, this study is aimed to firstly understand and describe to what extent the implementation of risk management in sharia financing in As Sakinah Cooperation Sidoarjo is, and secondly, to understand and describe the credit risk settlement scheme that occurs in sharia financing in As Sakinah Cooperation Sidoarjo.This research used qualitative method, using a case study approach. Data are collected through interview technique at main source and documents and regulation of the cooperation as secondary data source. The data were analyzed through 3 (three) steps. They are data deduction, data display and conclusion and verification.The results show that the role of the group and the joint responsibility system become the key in reducing credit riskÂ Keywords: management, risk, credit, Ijarah, Murabahah.